Factors associated with non-invasive mechanical ventilation failure in patients with hematological neoplasia and their association with outcomes - Barreto, Lídia Miranda (J Intensive Care, 2020)
BACKGROUND: The usefulness of non-invasive mechanical ventilation (NIMV) in oncohematological patients is still a matter of debate. AIM: To analyze the rate of noninvasive ventilation failure and the main characteristics associated with this endpoint in oncohematological patients with acute respiratory failure (ARF). METHODS: A ventilatory support protocol was developed and implemented before the onset of the study. According to the PaO(2)/FiO(2) (P/F) ratio and clinical judgment, patients received supplementary oxygen therapy, NIMV, or invasive mechanical ventilation (IMV). RESULTS: Eighty-two patients were included, average age between 52.1 ± 16 years old; 44 (53.6%) were male. The tested protocol was followed in 95.1% of cases. Six patients (7.3%) received IMV, 59 (89.7%) received NIMV, and 17 (20.7%) received oxygen therapy. ICU mortality rates were significantly higher in the IMV (83.3%) than in the NIMV (49.2%) and oxygen therapy (5.9%) groups (P < 0.001). Among the 59 patients who initially received NIMV, 30 (50.8%) had to eventually be intubated. Higher SOFA score at baseline (1.35 [95% CI = 1.12–2.10], P = 0.007), higher respiratory rate (RR) (1.10 [95% CI = 1.00–1.22], P = 0.048), and sepsis on admission (16.9 [95% CI = 1.93–149.26], P = 0.011) were independently associated with the need of orotracheal intubation among patients initially treated with NIMV. Moreover, NIMV failure was independently associated with ICU (P < 0.001) and hospital mortality (P = 0.049), and mortality between 6 months and 1 year (P < 0.001). CONCLUSION: The implementation of a NIMV protocol is feasible in patients with hematological neoplasia admitted to the ICU, even though its benefits still remain to be demonstrated. NIMV failure was associated with higher SOFA and RR and more frequent sepsis, and it was also related to poor prognosis.